In vivo identification of Drosophila rhodopsin interaction partners by biotin proximity labeling - Nilofar Feizy; Sarah Franziska Leuchtenberg; Christine Steiner; Berit Würtz; Leo Fliegner; Armin Huber (Scientific Reports, 2024)
Abstract Proteins exert their function through protein–protein interactions. In Drosophila, G protein-coupled receptors like rhodopsin (Rh1) interact with a G protein to activate visual signal transduction and with arrestins to terminate activation. Also, membrane proteins like Rh1 engage in protein–protein interactions during folding within the endoplasmic reticulum, during their vesicular transport and upon removal from the cell surface and degradation. Here, we expressed a Rh1-TurboID fusion protein (Rh1::TbID) in Drosophila photoreceptors to identify in vivo Rh1 interaction partners by biotin proximity labeling. We show that Rh1::TbID forms a functional rhodopsin that mediates biotinylation of arrestin 2 in conditions where arrestin 2 interacts with rhodopsin. We also observed biotinylation of Rh1::TbID and native Rh1 as well as of most visual signal transduction proteins. These findings indicate that the signaling components in the rhabdomere approach rhodopsin closely, within a range of ca. 10 nm. Furthermore, we have detected proteins engaged in the maturation of rhodopsin and elements responsible for the trafficking of membrane proteins, resembling potential interaction partners of Rh1. Among these are chaperons of the endoplasmic reticulum, proteins involved in Clathrin-mediated endocytosis as well as previously unnoticed contributors to rhodopsin transportation, such as Rab32, Vap33, or PIP82.